On-demand dissolution of modular, synthetic extracellular matrix reveals local epithelial-stromal communication networks. (June 2017) - Valdez, Jorge; Cook, Christi D.; Ahrens, Caroline Chopko; Wang, Alex J.; Brown, Alexander; Kumar, Manu; Stockdale, Linda; Rothenberg, Daniel; Renggli, Kasper; Gordon, Elizabeth; Lauffenburger, Douglas; White, Forest; et al.
Abstract: Methods to parse paracrine epithelial-stromal communication networks are a vital need in drug development, as disruption of these networks underlies diseases ranging from cancer to endometriosis. Here, we describe a modular, synthetic, and dissolvable extracellular matrix (MSD-ECM) hydrogel that fosters functional 3D epithelial-stromal co-culture, and that can be dissolved on-demand to recover cells and paracrine signaling proteins intact for subsequent analysis. Specifically, synthetic polymer hydrogels, modified with cell-interacting adhesion motifs and crosslinked with peptides that include a substrate for cell-mediated proteolytic remodeling, can be rapidly dissolved by an engineered version of the microbial transpeptidase Sortase A (SrtA) if the crosslinking peptide includes a SrtA substrate motif and a soluble second substrate. SrtA-mediated dissolution affected only 1 of 31 cytokines and growth factors assayed, whereas standard protease degradation methods destroyed about half of these same molecules. Using co-encapsulated endometrial epithelial and stromal cells as one model system, we show that the dynamic cytokine and growth factor response of co-cultures to an inflammatory cue is richer and more nuanced when measured from SrtA-dissolved gel microenvironments than from the culture supernate. This system employs accessible, reproducible reagents and facile protocols; hence, has potential as a tool in identifying and validating therapeutic targets in complex diseases. Graphical abstract: